Klasifikasi Patah Tulang Dasar Kepala - Ridhoni, Muhammad; Prasetyo, Eko; Lampus, Harsali L. (e-CliniC, 2021)
Abstract: Skull base fracture is a linear fracture that commonly occurs in the temporal cranium. Traumatic brain injury (TBI) often found and handled in the emergency department is head trauma and traffic accident is the main cause of base skull fracture. Approximately 25%-66% of traffic accidents cause fracture of the skull base according to the fracture site. This study was aimed to obtain the classification of skull base fractures and the most common types of classification. This was a literature review study using three databases, namely Google Scholar, ClinicalKey, and PubMed. Based on the inclusion and exclusion criteria, there were 14 literatures reviewed consisting of 1 retrospective study, 2 clinical reviews, 1 literature review, 3 review articles, 2 prospective studies, 3 case reports, 1 descriptive study, and 1 case study. These articles reviewed the classification of skull base fracture. The classification of each section was arranged based on the mechanism and location of skull base fractures. In conclusion, the classification of skull base fracture is divided into anterior, middle and posterior fossa cranii fractures. Fractures of the middle cranii fossa is the most common case and of the posterior cranii fossa is the rarest case.Keywords: traumatic brain injury (TBI); skull base fractures; fracture classificationÂ Â Abstrak: Patah tulang dasar kepala merupakan jenis fraktur linier yang umum terjadi pada bagian temporal kranium. Kasus trauma yang sering ditemukan dan ditangani di unit gawat darurat ialah trauma kepala. Kecelakaan lalu lintas (KLL) merupakan penyebab utama fraktur basis kranii. Sekitar 25-66% kasus KLL menyebabkan kejadian fraktur basis kranii sesuai lokasi fraktur. Penelitian ini bertujuan untuk mengetahui jenis klasifikasi patah tulang dasar kepala dan jenis klasifikasi yang paling sering terjadi. Jenis penelitian ialah suatu literature review. Literatur diperoleh dengan menggunakan beberapa database, seperti Google Scholar, ClinicalKey, dan PubMed. Berdasarkan kriteria inklusi dan eksklusi didapatkan 14 literatur terdiri atas 1 retrospective study, 2 clinical review, 1 literature review, 3 review article, 2 prospective study, 3 case report, 1 descriptive study, dan 1 case study. Hasil penelitian mendapatkan 14 literatur mengulas tentang klasifikasi patah tulang dasar kepala dan klasifikasi setiap bagian disusun berdasarkan mekanisme fraktur dan lokasi fraktur yang terjadi. Simpulan penelitian ini ialah secara garis besar klasifikasi patah tulang dasar kepala terbagi atas fraktur fossa kranii anterior, media, dan posterior. Kasus fraktur fossa kranii media merupakan kasus yang paling sering terjadi dan kasus fraktur fossa kranii posterior merupakan kasus yang paling jarang terjadi.Kata kunci: trauma kepala; patah tulang dasar kepala; klasifikasi fraktur